Application of the Constructivist Method and Its Implementation in Christian Religious Education at Paulus Theological Seminary Jakarta - Ndolu, Faransina (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2025)
This study examines the application of constructivist pedagogy within Christian Religious Education at Sekolah Tinggi Teologi Paulus Jakarta. Constructivism rooted in the work of Jean Piaget and Lev Vygotsky posits that knowledge is actively built by learners through experience, reflection, and social interaction rather than passively transferred from instructors. In theological education, this shift reframes lecturers as facilitators who scaffold students’ personal and communal engagement with Scripture and Christian doctrine. Employing a qualitative descriptive design that integrates literature review, non-participant observation, and semi-structured interviews with lecturers and students, the study finds that constructivist practices at STT Paulus Jakarta promote higher-order thinking, contextual biblical interpretation, and collaborative learning. Notwithstanding these benefits, challenges persist in lecturer readiness, student self-regulation, and resource availability. The paper argues that constructivism is both relevant and effective for Christian education, provided it is supported by institutional commitment to professional development and pedagogical innovation.